Table of Content - -, (Journal of Humanities & Social Sciences, 2023)
Table of Content:1. The role of the social worker in dealing with family disintegrationMrs. Sarah Hamid Al-Ahmadi2. Fashion designing simulating environmental art (the southern region) as one of the Small Enterprises to stimulate tourism according to the vision of 2030 for the Kingdom of Saudi ArabiaCo-Prof. Randa Monier Elkherbawy3. Cosmic justice between theory and practice in John Rawls' philosophyProf-lecturer \ Boussekek Abdelghani Ben Ali4. The intellectual activities of the Maghreb cinematic discourse: Attempts to understand reality and its manifestationsDr. Elmahmoudi Tarek5. The reality of Qualifying and Training Graduates of the Department of Library and Information Science - Sana’a University in line with the requirements of the labor market: Field studyDr. Merzah Ahmed Al-Assal6. Climate change's effects on women: Iraq as an exampleAsst-Teacher \ Ansam Ali Zghir7. Commissive Illocutionary Acts Found in Na’ima Robert’s She Wore Red TrainersMrs. Doa‘a Ali Mohammed Farhan Al-Sharabi , Prof. Abdusalam Mohammed Ghaleb Al-Ghrafy8. Three Major Stages in the Historical Development of TranslationDr. Ahmed Mohamed Lemine El-Mokhtar
Keywords: The Journal of Human and Social Sciences